IMPLIKASI HUKUM PEMBATASAN TIKTOK ANAK DI BAWAH 16 TAHUN TERHADAP KARIER ATLET E-SPORTS MOBILE LEGENDS - Hakim Arvadan, Yan; Widia Putri Dani; Nurhasan Ismail; Yuniarti Sani Damayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of the e-sports industry in Indonesia has made Mobile Legends: Bang Bang (MLBB) one of the most sought-after competitive disciplines, even among athletes under the age of 16. Meanwhile, TikTok has become an inseparable ecosystem for promotion, live streaming, and community interaction for young e-sports athletes. Government Regulation No. 17 of 2025 on the Governance of Electronic System Implementation for Child Protection (PP TUNAS) and the Minister of Communication and Digital Affairs Regulation No. 9 of 2026, which restrict social media access for children under 16, generate complex legal implications for the underage e-sports ecosystem in Indonesia. This study employs a normative juridical approach through library research and prescriptive analysis of primary, secondary, and tertiary legal materials. The findings identify three main legal implications: (1) tension between TikTok restrictions and athletes' career development rights under the National Sports System Law; (2) complexity of platform accountability and parental consent mechanisms; and (3) potential competitive asymmetry at the international level. TikTok restrictions for e-sports athletes under 16 represent a legally valid preventive protection measure, but require structured exception mechanisms based on parental consent, platform oversight, and collaboration with the national e-sports ecosystem to preserve both children's developmental rights and competitive integrity.